2021
DOI: 10.1002/macp.202100383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Chemical, Morphological and Dielectric Properties of Supramolecular Networks Consisting of Polyethylene Glycol Polyrotaxanes and Polystyrene/Semi‐Rotaxane with Hydroxypropyl‐β‐Cyclodextrins

Abstract: In the present study, the effect of 5, 10, and 15 wt% of polystyrene/ hydroxypropyl‐β‐cyclodextrins (PS/HPβCD) semi‐rotaxane (SR) incorporation in the polyethylene glycol/hydroxypropyl‐β‐cyclodextrins polyrotaxane (PEG/HPβCD) matrix is investigated. The changes of physico‐chemical, morphological, and dielectric properties of the composite materials were evaluated and compared to those of the pure crosslinked film. Scanning electron microscopy attests formation of porous film, whose average size diameters incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…After the swelling process, the pores values of films 2 and 3 were found to be 0.036 and 0.044 µm, respectively. This result indicated that with the increasing concentration of PI/HPβCD in the matrix, the porosity increases following the same trend identified in the case of the polystyrene/semi-rotaxane composite films [11]. These findings could be attributed to either the conformational changes in the polyrotaxanes as a result of their physical interactions or to the increased crystallinity generated via the PI chains, which was also found in the WAXS analysis.…”
Section: Physical and Morphological Properties Of The Materialssupporting
confidence: 75%
See 3 more Smart Citations
“…After the swelling process, the pores values of films 2 and 3 were found to be 0.036 and 0.044 µm, respectively. This result indicated that with the increasing concentration of PI/HPβCD in the matrix, the porosity increases following the same trend identified in the case of the polystyrene/semi-rotaxane composite films [11]. These findings could be attributed to either the conformational changes in the polyrotaxanes as a result of their physical interactions or to the increased crystallinity generated via the PI chains, which was also found in the WAXS analysis.…”
Section: Physical and Morphological Properties Of The Materialssupporting
confidence: 75%
“…In addition, the density of the pores increases with increasing concentration of PI/HPβCD SR in the matrix. The average pore sizes of the composite materials were estimated using the image J analysis software and the values were obtained after a statistical correction was applied [ 11 ]. The average pore diameters of the composite materials 2 and 3 before swelling were found to be 0.020 and 0.038 μm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects will be discussed later, in comparison with the corresponding dielectric spectroscopy data. As observed, no crystallization exothermal signal and neither endothermic correlations to the melting temperature are found, revealing that the PS NPs are entirely amorphous polymers [39]. The behavior of measured permittivity, ε , with frequency at room temperature is displayed in Figure 6 for four polystyrene samples.…”
Section: Glass Transition Temperaturementioning
confidence: 79%